On typification of Chenopodium acerifolium (Chenopodiaceae): an update and new epitypification - Mosyakin, Sergei L.; Shumilova, Alisa V. (Phytotaxa, 2018)
Various issues and problems of taxonomy and nomenclature of Chenopodium acerifolium Andrzejowski (1862: 132), including its typification, were recently discussed in detail by Mosyakin (2017). In short, the name C. acerifolium was effectively lectotypified by Dvořák (1987: 562, Fig. 1 on page 563; see also Mosyakin 2017) based on a specimen from KW[1] sent on loan to BRNU in the 1980s. Being probably unaware of that lectotype designation, Sukhorukov (2014: 227) designated as the lectotype another specimen that is currently deposited in LE. That specimen originated from the herbarium of W.S.J.G. Besser and later was part of the herbarium of F.E.L. Fischer (curatorial label: “Herb. Fischer. Chenopodium acerifolium Andrz. In ins. Borystheni Kiioviae. Herb. W. Besser”). The specimen from KW initially designated by Dvořák (1987) as the lectotype of C. acerifolium was reported missing (not found in KW or BRNU until 2017; see details in Mosyakin 2017). Mosyakin (2017: 142) also concluded that “until the specimen selected as the lectotype by Dvořák (1987) is found, the selection of a lectotype by Sukhorukov, unfortunately, should stand”. The specimen from LE lacked fruits and was only flowering (see Uotila & Lomonosova 2016: 235), and because of that Mosyakin (2017: 142) proposed the specimen KW001002780 with well-developed plants and a handwritten original description by Andrzejowski as the epitype supporting the lectotype from LE (standing type) selected by Sukhorukov.